(untitled) (Medico Legal Update, 2023)
In the research, various methods for developing latent fingerprints on various surfaces have been reported. This paper describes a new powdering method for the development of latent fingerprints that is simple and nontoxic and can be used on a variety of substrates. In this study, non-toxic, simple, and easily accessible turmeric powder and Neem powder were used, all of which are commercially available natural powders with a variety of domestic and traditional applications. These powders have been used to decipher latent fingerprints on ten different substrates, including glass, lamination sheet, transparency sheet, metal surface, wooden surface, plain paper, cardboard, plastic, tile, and steel. It has been discovered that it produces very clear results on most surfaces. The powders were used to give the best results on all surfaces except plain paper. The prints are clear with all the ridge characteristics present.